Den mobile ordbogsbruger - Simonsen, Henrik Køhler (Nordiske Studier i Leksikografi, 2018)
People are already mobile – but is lexicography as a discipline up for the mobile challenge? This article is based on empirical data from a survey of five teenagers, who were asked to look up five terms with a bilingual dic-tionary app. The empirical data showed how real teenage users interact with mobile phones and dictionary apps and seem to indicate that lexi-cography and mobile devices are not yet fully compatible in all situations.